Synergy of Islamic education in character building - Basri, Hasan; In'ami, Moh; Mustafa, Mustafa (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study employs a library research approach using flexible content analysis to examine qualitative data derived from books and journal articles published over the last two decades. The findings confirm that Islamic education plays a significant role in character building and requires revitalization through the strengthening of integrated educational practices. This can be achieved by implementing integrative and connected models within curriculum design and learning processes, as well as by fostering synergy among educational stakeholders based on the core values of Islamic teachings. Such efforts need to be supported by comprehensive and consistent political alignment across various sectors of life to facilitate the development of a generation with strong Islamic character. However, this study is limited in that it does not extend to the formulation of political policy frameworks that align education with broader social systems. Therefore, further research is needed to explore this dimension as a continuation of the present study.